PREDICTORS OF INDEPENDENT WALKING RECOVERY AFTER STROKE IN PATIENTS ADMITTED TO AN INTEGRATED STROKE UNIT - Flomin, Y.V.; Gurianov, V.G.; Guliaieva, M.V.; Kushnerenko, O.L.; Gavryliv, I.R.; Sokolova, L.I. (World of Medicine and Biology, 2021)
Walking unassisted is a key goal of post-stroke rehabilitation. The study aimed to determine the predictors of independent walking at the time of hospital discharge. Uni- and multivariate regression models were built on the basis of demographic, clinical, and laboratory data of 442 study participants (median age was 65.8 years, 43 % were women, 84 % – with cerebral infarction). In a univariate analysis, the subtype of stroke, age and sex of the patient, atrial fibrillation, stroke severity, disability, motor, and cognitive impairment, and elevated levels of inflammatory markers during hospitalization were significantly associated with the dependence while walking. Multivariate analysis revealed only four independent predictors: patient's age, the severity of initial neurological deficits, initial assessment of gait function, and very late onset of rehabilitation. If the reliability of the prognostic model is confirmed, its use can contribute to realistic treatment goals and optimal preparation for hospital discharge.
Keywords: cerebral stroke; post-stroke rehabilitation; walking; stroke unit; prediction of treatment outcomes; prognostic models